2015
DOI: 10.1038/srep13170
|View full text |Cite
|
Sign up to set email alerts
|

miR-378a-3p modulates tamoxifen sensitivity in breast cancer MCF-7 cells through targeting GOLT1A

Abstract: Breast cancer is a hormone-dependent cancer and usually treated with endocrine therapy using aromatase inhibitors or anti-estrogens such as tamoxifen. A majority of breast cancer, however, will often fail to respond to endocrine therapy. In the present study, we explored miRNAs associated with endocrine therapy resistance in breast cancer. High-throughput miRNA sequencing was performed using RNAs prepared from breast cancer MCF-7 cells and their derivative clones as endocrine therapy resistant cell models, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 68 publications
2
65
0
Order By: Relevance
“…Recently, miR-378a-3p has been reported to be down-regulated in various diseases including cancers [12][13][14]. Growing evidence has demonstrated that miR-378a-3p is involved in a wide range of biological functions and processes such as cell growth, cell cycle, migration, differentiation, metabolism and angiogenesis [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, miR-378a-3p has been reported to be down-regulated in various diseases including cancers [12][13][14]. Growing evidence has demonstrated that miR-378a-3p is involved in a wide range of biological functions and processes such as cell growth, cell cycle, migration, differentiation, metabolism and angiogenesis [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer, miR-378a inhibits colorectal cancer cell growth and colony formation, and induces cell cycle arrest [19]. In breast cancer, miR-378a modulates tamoxifen sensitivity in MCF-7 cells through targeting GOLT1A [18]. In organ fibrosis, miR378a is a negative regulator of TGF-β1 and down-regulation of miR-378a contributes to the development of cardiac fibrosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…miR-378a, down-regulated in a variety of diseases including cancers, has been reported to trigger various cellular functions such as cell growth, cell cycle and migration [17][18][19][20][21]. Recently, Nagalingam et al found that miR-378a inhibits cardiac fibrosis via TGF-β1-dependent paracrine mechanism [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, of the top 10 miRNAs down-regulated in spheroids, five miRNAs (miR-486-3p, miR-134-5p, miR-320a, miR-127-3p, and miR-377-3p) have been reported previously to be related to pancreatic cancer, and three of them were found playing an important role in drug resistance (miR320a) [22], cell proliferation (miR-377-3p) [23], or as a tumor suppressor (miR-127-3p) [24],while the other two miRNAs had no further study yet. Four miRNAs, miR-370-3p, miR-185-5p, miR-193a-5p and miR-378a-3p were all associated with chemoresistance and involved in other types of cancer [25][26][27][28]. While the rest haven't been researched in cancers.…”
Section: Panc-1 Spheroid Cells Have Higher Tumorigenic Potential In Vivomentioning
confidence: 99%